Purification and characterization of recombinant nattokinase from Bacillus subtilis R0H1 - Thuy Ngan, Nguyen Thi; Tuan, Le; Huong, Nguyen Lan (Vietnam Journal of Biotechnology, 2022)
Nattokinase (NK) is a fibrinolytic enzyme with the potential for fighting cardiovascular diseases (CVD) thanks to its antithrombotic, antihypertensive, anticoagulant, anti-atherosclerotic, and neuroprotective effects. Nattokinase was first discovered and purified from soybean fermented food by Bacillus subtilis natto. To enhance NK’s activity and simplify downstream processes, production of recombinant NK using several microbial expression systems such as Escherichia coli, B. subtilis, and Lactococcus lactic has been studied. Among all of them, B. subtilis is a prominent host for overproduction of functional proteins which can be secreted directly into the culture medium. In this study, recombinant NK from B. subtilis R0H1 was purified using two-step membrane filtration. Results showed 3.2-fold increase in activity and a recovery rate of more than 80%. Molecular weight of NK was approximately 28 kDa and its fibrinolytic degradation capacity was proved according to SDS-PAGE. The optimal pH and temperature of this NK were 8.5 and 55°C, respectively. The enzyme activity was boosted by Mg2+, Ca2+ and obviously inhibited by Co2+, Zn+2, Fe2+, and SDS. The apparent Km and Vmax with fibrin as the substrate were 3.08 mM and 6.7 nmol/min, respectively. The results suggested that membrane filtration is a useful method for purification of recombinant NK from B. subtilis R0H1. Therefore, application of membrane system is proposed to purify NK at the pilot scale. In addition, our findings indicated that recombinant NK produced in B. subtilis R0H1 showed high and stable proteolytic activity in slightly alkaline pH and at high temperature. It also exhibited strong fibrinolytic activity again both substrates: fibrinogen and fibrin.